Long‐acting second‐generation and oral antipsychotics for substance use disorders and psychotic symptoms: Prescribing attitudes among Italian psychiatrists. Issue 4 (22nd February 2021) - Corbo, Mariangela; Martinotti, Giovanni; Aguglia, Andrea; Salvi, Virginio; Amerio, Andrea; Calò, Salvatore; Fusar‐Poli, Laura; Serafini, Gianluca; Signorelli, Maria; Amore, Mario; Mencacci, Claudio; Di Sciascio, Guido; et al.
Abstract: Purpose: To explore Italian psychiatrists' attitudes toward the off‐label use of second generation antipsychotics (SGAs) in patients with substance use disorder and psychotic symptoms. Design and Methods: A sample of 300 Italian psychiatrists associated with the Italian Society of Neuropsychopharmacology was randomly selected to complete a survey about the off‐label prescription of SGAs. Findings: Oral aripiprazole (32.7%), olanzapine (30.2%), and quetiapine (25.2%) were considered "appropriate." Long‐acting antipsychoticss were generally considered "inappropriate." Practice Implications: Our findings reflect a substantial level of uncertainty and a lack of coherent clinical guidance within the realm of dual diagnosis treatment. Therefore, they emphasize the need to develop specific guidelines to improve the management of pharmacotherapy among this population.